Flow Dehydration and Hydrogenation of Allylic Alcohols: Application to the Waste‐Free Synthesis of Pristane. Issue 10 (15th March 2017) - Furuta, Akihiro; Hirobe, Yuki; Fukuyama, Takahide; Ryu, Ilhyong; Manabe, Yoshiyuki; Fukase, Koichi
Abstract : Hydroxy‐substituted sulfonic acid functionalized silica (HO‐SAS) in combination with THF containing a small amount of water as a solvent proved to be a reliable system for the dehydration of allylic alcohols. This process generally caused dehydration within 1 min through a column reactor charged with HO‐SAS. The flow dehydration was sequenced by flow hydrogenation, which resulted in the synthesis of pristane. A scalable flow synthesis of pristane was successfully performed and afforded 10 g of pristane after an operation of 2 h. We also performed dehydration and hydrogenation by using a mixed column of HO‐SAS and 10 % Pd/C. Abstract : Hydroxy‐substituted sulfonic acid functionalized silica (HO‐SAS) in combination with THF containing a small amount of H2 O as a solvent is a reliable system for the dehydration of allylic alcohols. This process generally causes dehydration within 1 min through a column reactor charged with HO‐SAS. The flow dehydration is sequenced by flow hydrogenation, which results in the synthesis of pristane.